Commonest location of traumatic ulcers in edentulous patients after denture insertion - Muhammad Aamir Ghafoor Chaudhary, Syed Hammad Azeem Rizvi, Afsheen Zakir, Rummana Aqeel, Faiza Awais, Syeda Mahnoor Rauf, Khezran Qamar (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To evaluate frequency of commonest location of traumatic oral ulcers after complete denture insertion and find out their association with age, gender and arch type. Study design: Cross sectional observational study Place and duration: Prosthodontic department of Islamic International Dental College, Riphah International University Islamabad, from 11th Feb.,2022 till 11th April 2022. Methodology: A sample of 150 completely edentulous patients were clinically checked for traumatic ulcer development after insertion of complete denture. Frequently involved anatomical sites were noted in both arches. Denture surfaces were assessed to find out the frequently existing denture problems responsible for ulcers. Results: Out of total 150 patients 37.3% with oral ulcers were males and 62.7 % were female. 61-70 years old age group reported with frequent ulcers 48.7%. Frequently observed oral ulcer site in maxilla was sulci 10.0% and in mandible was ridge 24.7%. Frequently observed denture problem responsible for ulcer formation was denture surface roughness 46.7%. Association with age, gender and arch type was significant; p<0.05. Conclusion: Frequent ulcers develop in mandibular arch as compared to maxilla and commonest sites of ulcer developments are the ridges and sulci. Old age and female predisposition have been seen in ulcer development. Keywords: Complete dentures, Mandibular arch, Maxillary arch, oral ulcers, traumatic ulcers, post insertion complains